Magnitude and Order are Both Relevant in SNARC and SNARC‐like Effects: A Commentary on Casasanto and Pitt (2019). Issue 7 (2nd July 2021) - Prpic, Valter; Mingolo, Serena; Agostini, Tiziano; Murgia, Mauro
Abstract: In a recent paper by Casasanto and Pitt (2019), the authors addressed a debate regarding the role of order and magnitude in SNARC and SNARC‐like effects. Their position is that all these effects can be explained by order, while magnitude could only account for a subset of evidence. Although we agree that order can probably explain the majority of these effects, in this commentary we argue that magnitude is still relevant, since there is evidence that cannot be explained based on ordinality alone. We argue that SNARC‐like effects can occur for magnitudes not clearly characterized by overlearned ordinality and that magnitude can prevail on order, when the two are pitted against each other. Finally, we propose that different interpretations of the role of order and magnitude depend on the interaction of stimulus properties and task demands.